2014
DOI: 10.1108/ijpdlm-01-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Effective sourcing strategies for perishable product supply chains

Abstract: Purpose -The purpose of this paper is to assess whether an existing sourcing strategy can effectively supply products of appropriate quality with acceptable levels of product waste if applied to an international perishable product supply chain. The authors also analyse whether the effectiveness of this sourcing strategy can be improved by including costs for expected shelf life losses while generating order policies. Design/methodology/approach -The performance of sourcing strategies is examined in a prototype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 23 publications
0
46
0
1
Order By: Relevance
“…Maintaining the balanced supply of raw milk to processing plant will be a challenge for private dairy firms (Kumar et al, 2012). What if analysis have been used by Rijpkema et al, (2014) to understand the trade-off between transportation costs, shortage costs, inventory costs, product waste, and expected shelf life losses and to determine the sourcing strategy for perishable food products. Interestingly we didn't find any study that uses real time data or subjective/qualitative data to optimize or prioritize procurement decision.…”
Section: Optimizing Procurementmentioning
confidence: 99%
“…Maintaining the balanced supply of raw milk to processing plant will be a challenge for private dairy firms (Kumar et al, 2012). What if analysis have been used by Rijpkema et al, (2014) to understand the trade-off between transportation costs, shortage costs, inventory costs, product waste, and expected shelf life losses and to determine the sourcing strategy for perishable food products. Interestingly we didn't find any study that uses real time data or subjective/qualitative data to optimize or prioritize procurement decision.…”
Section: Optimizing Procurementmentioning
confidence: 99%
“…[45] proposed that efficient information sharing among value chain partners and adaption of material flows, which have a positive effect on reducing food waste in the food value chain. [46] found that food waste can be reduced through taking shelf-life losses into consideration, if the result of standard cost parameters in poor product quality and large amounts of product waste were determined. Meanwhile, other researchers on food logistics have investigated the different areas of logistics that can help to reduce the food waste, for example, [47] conducted a simulation through using the information on the quality of products that provided by intelligent packaging, the results indicated that quality-controlled logistics can substantially reduce food waste.…”
Section: Thematic Analysis: Food Waste Prevention Strategiesmentioning
confidence: 99%
“…An interesting problem is the last mile delivery of perishable goods even though on this topic, relatively few papers exist in the scientific literature. Some authors [56][57][58][59][60] analyze the transport problems of perishable goods related to the stability and perturbations of parameters to have the appropriate quality (with acceptable levels of product waste). Furthermore, the inventory routing problems of perishable goods to reduce environmental impact and CO 2 emissions from vehicles, using time-windows, are considered.…”
Section: Last Mile Logisticsmentioning
confidence: 99%